2021
DOI: 10.3389/fcimb.2021.701820
|View full text |Cite|
|
Sign up to set email alerts
|

Brain Microvascular Endothelial Cell-Derived HMGB1 Facilitates Monocyte Adhesion and Transmigration to Promote JEV Neuroinvasion

Abstract: Infection with Japanese encephalitis virus (JEV) induces high morbidity and mortality, including potentially permanent neurological sequelae. However, the mechanisms by which viruses cross the blood-brain barrier (BBB) and invade into the central nervous system (CNS) remain unclear. Here, we show that extracellular HMGB1 facilitates immune cell transmigration. Furthermore, the migration of immune cells into the CNS dramatically increases during JEV infection which may enhance viral clearance, but paradoxically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Studies on the interaction between human brain endothelial cells and Flaviviruses have demonstrated CNS invasion by direct infection of these cells and suggest that the BBB is a key gateway for arbovirus brain infections. For instance, JEV and ZIKV are able to infect cerebral endothelial cells and cross the BBB [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the interaction between human brain endothelial cells and Flaviviruses have demonstrated CNS invasion by direct infection of these cells and suggest that the BBB is a key gateway for arbovirus brain infections. For instance, JEV and ZIKV are able to infect cerebral endothelial cells and cross the BBB [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many flavivirus infections, especially DENV infection, a hallmark of viral pathogenesis leading to severe disease is alterations in the barrier function of the endothelium, resulting in transient vascular leak and hypotension that can lead to shock and potentially death [2, [54][55][56]. DENV, WNV, JEV, and ZIKV can alter the integrity of TJ/AJ proteins at the blood-brain and placental barriers [23,[57][58][59][60][61][62][63][64][65][66]. The altered expression and/or distribution of IJC proteins such as VE-cadherin, ZO-1, and β-catenin has been described in in vitro assays with epithelial and endothelial cells after DENV or other flaviviral infections [59][60][61][62][63][64][65][67][68][69][70][71], stimulation of human ECs with soluble factors circulating in sera from dengue patients [72][73][74] or secreted from DENV-infected cells [18,75], as well as in DENV and ZIKV NS1-stimulated umbilical vein ECs, ex vivo human chorionic explants, and dermal ECs [10,23,39,40,58,76,77].…”
Section: Discussionmentioning
confidence: 99%
“…DENV, WNV, JEV, and ZIKV can alter the integrity of TJ/AJ proteins at the blood-brain and placental barriers [23,[57][58][59][60][61][62][63][64][65][66]. The altered expression and/or distribution of IJC proteins such as VE-cadherin, ZO-1, and β-catenin has been described in in vitro assays with epithelial and endothelial cells after DENV or other flaviviral infections [59][60][61][62][63][64][65][67][68][69][70][71], stimulation of human ECs with soluble factors circulating in sera from dengue patients [72][73][74] or secreted from DENV-infected cells [18,75], as well as in DENV and ZIKV NS1-stimulated umbilical vein ECs, ex vivo human chorionic explants, and dermal ECs [10,23,39,40,58,76,77]. Importantly, IJC proteins have been found to circulate in the serum of dengue patients undergoing severe plasma leakage, and alterations of the IJC have been proposed as potential biomarkers for disease prognosis [15,22,78].…”
Section: Discussionmentioning
confidence: 99%
“…High mobility group protein b1 (HMGB1) is a ubiquitous nuclear protein that is released extracellularly after cell activation, stress, injury, or apoptosis and plays an important role in neurodegenerative diseases by mediating neuroinflammation 103,104 ;…”
Section: Diabetes-related Cognitive Decline and Pyroptosismentioning
confidence: 99%